Spelling deficits in children with intellectual disabilities: Evidence from a regular orthography - Di Blasi, Francesco Domenico; Vizzi, Francesca; Stimoli, Maria Agatina; Buono, Serafino; Iaia, Marika; Zoccolotti, Pierluigi; Angelelli, Paola (Frontiers in Psychology, 2023)
In the present research project, we compared the spelling skills of a group of Italian children with intellectual disabilities (ID) to those of typically developing children matched for school level. In the first study, we analysed the spelling performance on a Passage Dictation Test. Forty-four children with ID, attending regular classrooms from 4th to 8th grades (with a mean age of 12.16 years; SD = 1.57), were compared with controls matched for sex and grade. Children with ID showed generally lower spelling performance in the dictation test. Furthermore, they showed a higher number of phonological (and phonetic-phonological) errors than phonologically plausible ones, indicating, as a group, predominant phonological difficulties as compared to lexical-orthographic ones. In a second study, a Words and Nonwords Dictation Test was administered (with stimuli varying for lexicality, orthographic complexity, regularity of transcription, and the presence of different types of phonetic-phonological difficulties). Twenty-two children with ID, all attending regular classrooms from 4th to 8th grades (with a mean age of 12.2 years; SD = 1.37), were compared to 22 controls matched for sex and grade. Children with ID underperformed on regular stimuli presenting specific types of phonetic-to-phonological difficulties (geminates, non-continuant consonants) and committed more minimal distance, context-sensitive and simple conversion misspellings. However, in a proportion of children, there were also deficits in the orthographic-lexical procedure, as indicated by a low performance in words with unpredictable spelling. It is concluded that children with ID have significant spelling difficulties not confined to the orthographic process but also to the phoneme-to-grapheme mapping, that in a regular language like Italian, should be acquired early and easily.